2014
DOI: 10.1073/pnas.1402846111
|View full text |Cite
|
Sign up to set email alerts
|

Maximization, learning, and economic behavior

Abstract: The rationality assumption that underlies mainstream economic theory has proved to be a useful approximation, despite the fact that systematic violations to its predictions can be found. That is, the assumption of rational behavior is useful in understanding the ways in which many successful economic institutions function, although it is also true that actual human behavior falls systematically short of perfect rationality. We consider a possible explanation of this apparent inconsistency, suggesting that mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
104
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 78 publications
3
104
0
Order By: Relevance
“…Research on reinforcement-based learning in iterated games suggests that, to maximize their payoffs, disputants and third parties need to repeatedly experience circumstances where they make the optimal choice and receive the best possible payoff (24). Allowing disputants and third parties to interact repeatedly may reveal that decisions based on experienced outcomes diverge from decisions based on described payoffs.…”
Section: Discussionmentioning
confidence: 99%
“…Research on reinforcement-based learning in iterated games suggests that, to maximize their payoffs, disputants and third parties need to repeatedly experience circumstances where they make the optimal choice and receive the best possible payoff (24). Allowing disputants and third parties to interact repeatedly may reveal that decisions based on experienced outcomes diverge from decisions based on described payoffs.…”
Section: Discussionmentioning
confidence: 99%
“…This is a worldwide platform that connects skilled workers, who are willing to work on a temporary contract basis, with those seeking to employ them. I conceptualize hiring as a dynamic experiential learning process (Denrell andLeMens 2007, Erev andRoth 2014) and investigate hiring by an employer as a sequence of events that occurs, repeatedly, over time.…”
mentioning
confidence: 99%
“…Empirical studies have found that people may deviate (28), although deviations are reduced by learning (16). Hence, it will be useful to explain the desirability of equilibrium to agents.…”
Section: Discussion Of the Assumptionsmentioning
confidence: 99%